Correlations of soluble TRAILR4, white blood cell count, and 25-hydroxyvitamin D with acute upper respiratory infection in children - Wu, Lianfang; Chen, Zhengjie; Hu, Jiakai (Vojnosanitetski pregled, 2025)
Background/Aim. Rapid diagnosis and treatment guidance for acute upper respiratory infection (AURI) are challenging due to difficulties in specimen collection and the need for advanced laboratory conditions. The aim of this study was to investigate the correlations between soluble tumor necrosis factor-related apoptosis-inducing ligand receptor 4 (sTRAILR4), white blood cell (WBC) count, and 25-hydroxyvitamin D [25(OH)D] with AURI in children. Methods. A total of 80 children with AURI treated from January 2022 to January 2023 were enrolled in the study group. Another 80 healthy children undergoing physical examinations during the same period were enrolled in the control group. The levels of serum sTRAILR4 and 25(OH)D, and WBC count were measured. Receiver operating characteristic (ROC) curves were plotted to analyze the predictive values of serum sTRAILR4 and 25(OH)D levels and WBC count for AURI. Unconditional logistic stepwise regression analysis was employed for multivariate analysis. Results. Compared with the control group, the study group had a significantly elevated level of sTRAILR4 and WBC count and a reduced level of 25(OH)D (p < 0.05). The areas under the ROC curves of sTRAILR4 and 25(OH)D levels, and WBC count were 0.893, 0.765, and 0.937, respectively, suggesting that they were predictors of AURI. An elevated level of sTRAILR4 (≥ 88.751 pg/mL), elevated WBC count (≥ 10.223 × 109/L), along with a reduced level of 25(OH)D (≤ 48.943 nmol/L), were identified as significant influencing factors for AURI (p < 0.05). The level of sTRAILR4 and WBC count were positively correlated with AURI, while the 25(OH)D level had a negative correlation (p < 0.05). Conclusion. The children with AURI have a significantly higher level of sTRAILR4 and WBC count and a lower level of 25(OH)D than healthy children. In addition to WBC, sTRAILR4 and 25(OH)D may have a role in the assessment of pediatric upper respiratory infection.
Keywords: child; leukocytes; respiratory tract infections; tumor necrosis factor – alpha; vitamin d